Economic Growth and The Quality of Environment: Evidence of The Environmental Kuznets Curve (EKC) in Indonesia - Idris, Idris; Sari, Yollit Permata (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2022)
This study proved the EKC hypothesis results of the trade-off between economic growth and environmental degradation in Indonesia. The researchers used the non-linear quadratic regression estimation. This study found that the EKC hypothesis was almost valid in all islands in Indonesia, such as Sumatra Island, Sulawesi Island, Borneo Island, and Small Island in the Eastern Region of Indonesia. Thus, the economic growth causes the environmental gradation while the trade-off did not apply in Java and Bali. Government policies regarding the environment and globalization played an important role in generating and transferring production technology that saved resources and used cleaner technology from developed countries to developing countries so the EKC hypothesis does not apply in Indonesia.